2010
DOI: 10.4049/jimmunol.1000288
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Enhances Effector Th1 Cell Activation but Promotes Self-Regulation via IL-10

Abstract: Myelin-specific effector Th1 cells are able to perpetuate CNS inflammation in experimental autoimmune encephalomyelitis, an animal model representative of multiple sclerosis. Although the effects of cytokines in the CNS microenvironment on naive CD4+ T cells have been well described, much less is known about their ability to influence Ag-experienced effector cells. TGF-β is a multifunctioning cytokine present in the healthy and inflamed CNS with well-characterized suppressive effects on naive T cell functions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 48 publications
3
51
0
1
Order By: Relevance
“…The T-bet-dependent maturation of IELPs was intriguing as thymic IELP development also depends on TGF-b (Konkel et al, 2011), which is a known inhibitor of T-bet in Th1 cell differentiation (Gorelik et al, 2002;Huss et al, 2010). Accordingly, IELP in vitro culture with the addition of TGF-b demonstrated that TGF-b inhibits the induction of T-bet in IELPs ( Figure S5D).…”
Section: Il-15 Induced Expansion and Differentiation Of Thymic Ielps mentioning
confidence: 88%
“…The T-bet-dependent maturation of IELPs was intriguing as thymic IELP development also depends on TGF-b (Konkel et al, 2011), which is a known inhibitor of T-bet in Th1 cell differentiation (Gorelik et al, 2002;Huss et al, 2010). Accordingly, IELP in vitro culture with the addition of TGF-b demonstrated that TGF-b inhibits the induction of T-bet in IELPs ( Figure S5D).…”
Section: Il-15 Induced Expansion and Differentiation Of Thymic Ielps mentioning
confidence: 88%
“…Thus, suppression of the TGFb pathway enhances T-bet expression, as well as promotes the differentiation of pathogenic Th17 cells, suggesting that miRNAs that suppress TGFb signalling may promote the development of autoreactive effector T cells. Furthermore, differentiation of human Th17 occurs independently of TGFb (Acosta-Rodriguez et al, 2007;Wilson et al, 2007), and TGFb induces IL-10 expression in autoreactive Th1 cells, promoting a self-regulation mechanism (Huss et al, 2010). IL-10 production has been shown to be impaired in patients with multiple sclerosis (Cao et al, 2015), but positively associated with therapeutic benefit (Du Pasquier et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, diminished TGFb signalling would potentially allow encephalitogenic Th1 cells to mediate pathology more robustly due to a lack of inherent regulation. As TGFb signalling not only promotes Treg development, but also influences the differentiation of naïve T cells into effector T cells and suppresses the function of effector/memory T cells (Huss et al, 2010), the TGFb-targeting miRNAs may have the potential to influence naïve T cell activation in our inducible Treg differentiation assays. However, the percentage of naïve CD4 T cells that remain unactivated increases when inducible Treg differentiation is suppressed in miRNA-transfected naïve CD4 T cells, suggesting that an increase in naïve T cell activation in miRNA-transfected PBMCs is not skewing the percentage of inducible Tregs observed.…”
Section: Discussionmentioning
confidence: 99%
“…Several immunoregulatory molecules, such as IL-10, TGF-ß, and indoleamine 2,3-dioxygenase (IDO), can support T REG function [3,4,6,7]. In particular, IL-10 plays a role in the development and immunosuppressive function of several T REG cell types [2] and is a crucial protective cytokine in several autoimmune diseases [3].…”
Section: Introductionmentioning
confidence: 99%